PENGARUH UKURAN PERUSAHAAN, LEVERAGE, STRUKTUR MODAL DAN KEIAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2020 - Diyah Puspita Handayani; I Wayan Sukadana; I Wayan Suarjana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
In today's increasingly rapid development of the business world, companies are required to be able to survive in the competition. Companies are required to be able to provide the best performance to their stakeholders so that they can continue to provide benefits to their stakeholders. This is in accordance with the purpose of establishing the company. This study aims to examine and obtain empirical evidence of the effect of Firm Size, Leverage, Capital Structure and Dividend Policy on the Value of Companies listed on the Indonesia Stock Exchange in 2018-2020. The population in this study are manufacturing companies in the food and beverage sector listed on the Indonesia Stock Exchange in 2018-2020. The sample in this study were 19 companies which were determined based on the purposive sampling method. The analytical tool used to test the hypothesis is the F test and T test. The results showed that firm size had a negative and insignificant effect on firm value. Leverage has a negative and insignificant effect on firm value. Capital structure has a negative and insignificant effect on firm value. Dividend policy has a positive and significant effect on firm value. Further research can develop this research with other variables.